The role of anti-hypertensive treatment, comorbidities and early introduction of LMWH in the setting of COVID-19: A retrospective, observational study in Northern Italy. (1st February 2021) - Desai, Antonio; Voza, Giuseppe; Paiardi, Silvia; Teofilo, Francesca Ilaria; Caltagirone, Giuseppe; Pons, Marta Ripoll; Aloise, Monia; Kogan, Maria; Tommasini, Tobia; Savevski, Victor; Stefanini, Giulio; Angelini, Claudio; et al.
Abstract: Background: There is a great deal of debate about the role of cardiovascular comorbidities and the chronic use of antihypertensive agents (such as ACE-I and ARBs) on mortality on COVID-19 patients. Of note, ACE2 is responsible for the host cell entry of the virus. Methods: We extracted data on 575 consecutive patients with laboratory-confirmed SARS-CoV-2 infection admitted to the Emergency Department (ED) of Humanitas Center, between February 21 and April 14, 2020. The aim of the study was to evaluate the role of chronic treatment with ACE-I or ARBs and other clinical predictors on in-hospital mortality in a cohort of COVID-19 patients. Results: Multivariate analysis showed that a chronic intake of ACE-I was associated with a trend in reduction of mortality (OR: 0.53; 95% CI: 0.27–1.03; p  = 0.06), differently from a chronic intake of ARB (OR: 1.1; 95% CI: 0.5-2.8; p=0.8). Increased age (ORs ranging from 3.4 to 25.2 and to 39.5 for 60–70, 70–80 and >80 years vs <60) and cardiovascular comorbidities (OR: 1.90; 95% CI: 1.1–3.3; p  = 0.02) were confirmed as important risk factors for COVID-19 mortality. Timely treatment with low-molecular-weight heparin (LMWH) in ED was found to be protective (OR: 0.36; 95% CI: 0.21–0.62; p  < 0.0001). Conclusions: This study can contribute to understand the reasons behind the high mortality rate of patients in Lombardy, a region which accounts for >50% of total Italian deaths. Based on our findings, we support that daily intake of antihypertensive medications in the setting of COVID-19 should not be discontinued and that a timely LMWH administration in ED has shown to decrease in-hospital mortality. Highlights: This is a retrospective study on 575 consecutive patients with laboratory-confirmed SARS-CoV-2 infection from a center in Northern Italywhose whose in-hospital mortality was 20.9%. Chronic treatment with ACEI in COVID-19 patients is associated with a decrease and a significant delay in in-hospital mortality, differently from the chronic use of ARBs. Increasing age and cardiovascular comorbidities are important risk factors for Covid-19 mortality, while an early introduction of LMWH in the setting of Covid-19 leads to a better prognosis.